2007
DOI: 10.1111/j.1095-8649.2007.01434.x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of de‐calcification procedures for δ13C and δ15N analysis of yellow perch, walleye and Atlantic salmon scales

Abstract: The scales of three species of fishes, yellow perch Perca flavescens, walleye Sander vitreus and Atlantic salmon Salmo salar, were acidified and the isotopic signatures were compared to nonacidified scales from the same fishes. No significant acidification effects on either carbon or nitrogen isotope signatures were found. Results contrast with earlier literature findings noting significant acidification effects and suggest acidification tests be undertaken before scales are used for temporal reconstruction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 18 publications
1
25
1
Order By: Relevance
“…Hydrobiologia (2010) and nitrogen) on whitefish (C. lavaretus; Perga & Gerdeaux, 2003), small but biologically irrelevant effects on roach (Syväranta et al, 2008) and no effects after scale acidification on yellow perch (P. flavescens), walleye (S. vitreus), Atlantic salmon (S. salar; Sinnatamby et al, 2007) and North American whitefish (Coregonus clupeaformis; Rennie et al, 2009). Variability in among species scale characteristics might be one of the explanations for the differences occurring in our study and the other published studies.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Hydrobiologia (2010) and nitrogen) on whitefish (C. lavaretus; Perga & Gerdeaux, 2003), small but biologically irrelevant effects on roach (Syväranta et al, 2008) and no effects after scale acidification on yellow perch (P. flavescens), walleye (S. vitreus), Atlantic salmon (S. salar; Sinnatamby et al, 2007) and North American whitefish (Coregonus clupeaformis; Rennie et al, 2009). Variability in among species scale characteristics might be one of the explanations for the differences occurring in our study and the other published studies.…”
Section: Discussioncontrasting
confidence: 69%
“…Syväranta et al (2008) found significant effects of acidification on roach d 13 C, although they were smaller than the analytical error of the instrument and therefore biologically irrelevant. Sinnatamby et al (2007) in yellow perch (Perca flavescens), walleye (Sander vitreus) and Atlantic salmon (Salmo salar) and Rennie et al (2009) in North American whitefish found no significant acidification effects, though the former argued that there might be a species-specific difference in the response to acid treatment.…”
Section: Introductionmentioning
confidence: 94%
“…In contrast to data presented by others investigating European populations of Wsh (Syvaranta et al 2008;Perga and Gerdeaux 2003), we found no signiWcant eVect of acid treatment on scale 13 C signatures. AcidiWcation of scales has been shown to have little eVect in other North American Wsh species as well (Sinnatamby et al 2007), and a recent study on roach (Rutilus rutilus) showed an enrichment of only 0.14% with regards to 13 C after acidiWcation (Syvaranta et al 2008). This discrepancy among multiple studies may suggest geographic diVerences in the carbonate content of scales between Wsh species and/ or populations.…”
Section: Discussionmentioning
confidence: 96%
“…This was because whilst there is some conjecture within the literature over whether this procedure is necessary for scales (e.g. Hutchinson & Trueman, 2006;Sinnatamby et al, 2007), even where this is completed, then the extent of acidification on d 13 C tends to be small. For example, Ventura and Jeppesen (2010) found that the mean shift in d 13 C in six freshwater fishes (including four fishes of the Cyprinidae) following acid treatment was 0.18 ± 0.12%.…”
Section: Stable Isotope Analysismentioning
confidence: 99%